2020
DOI: 10.1186/s13054-020-03199-5
|View full text |Cite
|
Sign up to set email alerts
|

The obesity paradox in critically ill patients: a causal learning approach to a casual finding

Abstract: Background: While obesity confers an increased risk of death in the general population, numerous studies have reported an association between obesity and improved survival among critically ill patients. This contrary finding has been referred to as the obesity paradox. In this retrospective study, two causal inference approaches were used to address whether the survival of non-obese critically ill patients would have been improved if they had been obese. Methods: The study cohort comprised 6557 adult criticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 32 publications
1
28
0
2
Order By: Relevance
“…The prevalence of obesity is high in the ICU, ranging from 19% to 66% of critically ill patients. 1,2 Obesity seems to be associated with lower mortality in the critically ill patients but increases the risk of complications in several organ systems. 3 Previous studies have suggested a high incidence of community-acquired and health-care-associated infections in obese patients.…”
mentioning
confidence: 99%
“…The prevalence of obesity is high in the ICU, ranging from 19% to 66% of critically ill patients. 1,2 Obesity seems to be associated with lower mortality in the critically ill patients but increases the risk of complications in several organ systems. 3 Previous studies have suggested a high incidence of community-acquired and health-care-associated infections in obese patients.…”
mentioning
confidence: 99%
“…In some studies, obese patients have been shown to have equivocal, or even improved outcomes compared to non-obese patients, 26 , 27 whereas others have questioned the validity of this observation when appropriate statistical controls were implemented. 28 Whereas obesity places patients at risk for hypertension, diabetes, heart disease, and other disease in the normal population, the reasons why obesity in critically ill patients is associated with lower mortality in the critically ill is not fully understood. 27 , 29 Potential explanations for the obesity paradox in critically ill patients may be related to anti-inflammation, higher energy reserves, greater endotoxin neutralization, increased adrenal steroid synthesis, renin-angiotensin system activation, cardioprotective metabolic effects, and prevention of muscle wasting in the obese.…”
Section: Discussionmentioning
confidence: 99%
“…Eine „Dose-Response“-Metaanalyse von 31 Studien mit 238.961 Patient*innen konnte nur bis zu einem BMI ≤ 35 kg/m 2 protektive Wirkungen identifizieren, während ein BMI > 35 kg/m 2 mit einer signifikant erhöhten Letalität einherging [ 17 ]. In einer Studienkohorte von 6357 Patient*innen konnten keine signifikanten Vorteile für kritisch kranke Adipositaspatient*innen (18,9 % der Fälle) identifiziert werden [ 18 ].…”
Section: Erhebung Des Ernährungszustandsunclassified